Genetic diversity of Theileria orientalis from cattle in Turkey - Ozubek, Sezayi; Aktas, Munir (Elsevier Sci Ltd, 2019)
Theileria orientalis is usually a benign parasite but some genotypes cause infection and economic losses to the cattle industry. This study was carried out to determine T. orientalis genotypes in cattle. T. orientalis positive 63 sample were analyzed by amplifying the MPSP gene region by PCR. As a result of the SSCP analysis, samples with different band profiles were sent to the sequence analysis and genotypes were determined. T. orientalis genotype-specific PCR was performed to determine the mix genotypes. Type 1 (chitose), type 3 and type 1-type 3 mix were found positive 11.1%, 46%, and 17.5% respectively. In addition, phylogenetic analysis was performed to separate the chitose genotypes, and two samples were found in chitose A, one sample was found in chitose B. Although chitose A genotype is suggested to be more pathogenic than chitose B, but there is little evidence for this. As a result of this study, we showed the presence of pathogenic genotype T. orientalis in Turkey. Therefore, extensive epidemiological studies are required to understand the geographic distribution, different genotypes and clinical pathologies of T. orientalis.
Keywords: Theileria orientalis; Cattle; Genotype; PCR; SSCP